Sentinel lymph node diagnostic in prostate carcinoma: Part I: Technique and clinical evaluation - Vogt, H.; Wawroschek, F.; Wengenmair, H.; Wagner, T.; Kopp, J.; Dorn, R.; Gröber, S.; Heidenreich, P. (Nuklearmedizin - NuclearMedicine, 2002)
Aim: Evaluation of the significance of lymphoscintigraphy and intraoperative probe measurement for the identification of the sentinel lymph node (SLN) in prostate cancer. Patients and method: In 117 patients with prostate cancer scintigrams in various projections were acquired till approximately 6 hours p.i. after ultrasound guided transrectal intraprostatic injection of 99mTc-Nanocoll ®. On the following day the SLNs were identified in the operation theatre with a gamma probe and removed. Pelvic standard lymph node dissection followed SLNE. Results: In three of 117 patients with preoperative lymphoscintigraphy no SLN was scintigraphically detectable. These three patients had antecedent transurethral resection of the prostate. In 113 of the residual 114 patients SLN could be intraoperatively localized. In the mean four SLNs per patient were removed. 28 of 117 patients had pelvic lymph node metastases. In 25 cases SLN were right-positive, in one false-negative and in one intraoperatively not detectable. In one patient we found macrometastasis of up to 4 cm diameter (one SLN was tumour positive). In 15 cases only the SLN was bearing tumour. Conclusion: The SLNE with preoperative lymphoscintigraphy and intraoperative gamma probe measurement is suitable for detecting lymph node metastasis in prostate cancer. SLNE is superior to the surgical techniques commonly used in pelvic lymphadenectomy.
Keywords: Prostate cancer; sentinel lymph node